2020
DOI: 10.1097/sla.0000000000004463
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Failure to Rescue After Inpatient Pediatric Surgery

Abstract: Objective: To describe the frequency and patterns of postoperative complications and FTR after inpatient pediatric surgical procedures and to evaluate the association between number of complications and FTR. Summary and Background: FTR, or a postoperative death after a complication, is currently a nationally endorsed quality measure for adults. Although it is a contributing factor to variation in mortality, relatively little is known about FTR after pediatric surgery. Methods: Cohort study of 200,554 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 37 publications
1
29
1
Order By: Relevance
“…Measuring quality in pediatric surgery remains a challenge due to the overall low rate of adverse outcomes, such as postoperative complications and mortality. [5][6][7][8] Previous pediatric QI initiatives have addressed this limitation by prioritizing high yield targets representing a significant burden of pediatric morbidity and health care costs, such as appendicitis, gastrostomy, colorectal procedures, and specific neonatal conditions (eg, CDH, gastroschisis). 9,13 In this context, our study aimed to identify potential high-priority targets for the development of future QI projects in the pediatric surgical population and our findings offer several novel conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring quality in pediatric surgery remains a challenge due to the overall low rate of adverse outcomes, such as postoperative complications and mortality. [5][6][7][8] Previous pediatric QI initiatives have addressed this limitation by prioritizing high yield targets representing a significant burden of pediatric morbidity and health care costs, such as appendicitis, gastrostomy, colorectal procedures, and specific neonatal conditions (eg, CDH, gastroschisis). 9,13 In this context, our study aimed to identify potential high-priority targets for the development of future QI projects in the pediatric surgical population and our findings offer several novel conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with recent data demonstrating approximately a third of all pediatric deaths are not preceded by a coded complication in NSQIP-P, our study identified less than half of infant perioperative mortality was preceded by a postoperative complication. 7,8,11 As such, while FTR could potentially represent a promising target for appropriately chosen disease processes, additional work is needed to understand the relationship between FTR and pediatric surgical quality across hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much is known about the incidence of FTR (Portuondo et al, 2020, Massarweh et al, 2016, Rosero et al, 2020, Chung et al, 2017, Ghaferi et al, 2009b, Sheetz et al, 2013, Ghaferi et al, 2009a, factors affecting its prevalence (Wakeam et al, 2014a, Blegen et al, 2013, Ghaferi et al, 2011, Johnston et al, 2015b, Sheetz et al, 2016, and potential causes and contributory factors (Burke et al, 2020, Johnston et al, 2015a, Johnston et al, 2014. The latter include potential failure of the following: to notice that the patient is unwell, to measure vital signs, to calculate early warning scores correctly, to check notes, to escalate in a timely fashion or to arrange definite care management.…”
Section: Discussionmentioning
confidence: 99%
“…FTR has been proposed as an alternative metric for surgical quality as opposed to mortality rate (Silber et al, 2007), because it is more tightly linked to postsurgical complication rates (Ghaferi et al, 2009b, Ghaferi et al, 2011, rather than patient factors. Across surgical settings, FTR rates have been found to range between 8% -18% (Johnston et al, 2015b, Portuondo et al, 2020.…”
Section: Failure To Rescue As a Surgical Quality Indicatormentioning
confidence: 99%